CRITICAL ANALYSIS OF MIDWIFERY CARE MODELS IN EVALUATING CONTINUITY OF CARE, PATIENT SATISFACTION, AND MATERNAL-INFANT HEALTH OUTCOMES - Mana Salem Mohammad ALReshan, Hamad Salem MoammedAlreshan, Saleh Salem Mohammad Al Rashan, Malfouf Nasser Alhozobar, MuniraFarisMasoud AL Mahri, SamiaRafeaAlsqoor, Hannoda Essa Saeed Al Yami (Chelonian Research Foundation, 2022)
Midwifery care models have increasingly emerged in maternal health care provision and are becoming at the forefront of maternal care service delivery. Unlike tissue donation, which involves donating body organs or parts, organ donation is more complex and expensive. Weorgan donation requires more resources than tissue donation. This essay focuses on midwifery care models and their effect on patients' continuous care, patient satisfaction, and maternal-infant health. Utilizing a conceptive literature survey and empirical studies analysis with the aid of charts, graphs, and figures, this analysis cites the advantages and shortcomings and identifies areas for midwifery care model improvement. This underlines the pricelessness of midwifery supervision in the birth process, neonatal and maternal health outcomes, and patient satisfaction. Proposals for enhancing the efficiency and effectiveness of midwifery care models by integrating community health workers and promoting seamless collaboration between healthcare professionals are proposed. Keywords: midwifery practice models, continuity of care, patient? Satisfaction, maternal-infant health outcomes, and care-patient-centered